2015
DOI: 10.1093/bmb/ldv043
|View full text |Cite
|
Sign up to set email alerts
|

The development of urban community health centres for strengthening primary care in China: a systematic literature review

Abstract: Future prospective studies should aim to provide solutions for strengthening the leading role of CHCs in providing equitable care in response to population ageing and multimorbidity challenges.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
90
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(96 citation statements)
references
References 35 publications
3
90
0
Order By: Relevance
“…To improve current efforts, providers may wish to examine the feasibility of incorporating family/friends into their patient’s healthcare plans. To ensure stronger linkages between provider, household, and PLCDs, policymakers may want to shift their focus towards primary hospitals and seek to ensure that primary hospitals are the managers of long-term treatment plans [39]. This shift can be enabled through strategic mass media campaigns at the community level so as to enhance public awareness of localized chronic disease maintenance [39,40,41].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To improve current efforts, providers may wish to examine the feasibility of incorporating family/friends into their patient’s healthcare plans. To ensure stronger linkages between provider, household, and PLCDs, policymakers may want to shift their focus towards primary hospitals and seek to ensure that primary hospitals are the managers of long-term treatment plans [39]. This shift can be enabled through strategic mass media campaigns at the community level so as to enhance public awareness of localized chronic disease maintenance [39,40,41].…”
Section: Discussionmentioning
confidence: 99%
“…To ensure stronger linkages between provider, household, and PLCDs, policymakers may want to shift their focus towards primary hospitals and seek to ensure that primary hospitals are the managers of long-term treatment plans [39]. This shift can be enabled through strategic mass media campaigns at the community level so as to enhance public awareness of localized chronic disease maintenance [39,40,41]. Our study also found, consistent with other studies [14,42], that elderly participants sought health services more regularly than younger participants.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown a much lower prevalence of exclusive breastfeeding in infants—35% of infants under 4 months of age were exclusively breastfed in Jinan City, China (2000) [8]; less than 5% infants were exclusively breastfed in the first 6 months of life in Zhejiang province, China (2005) [9]; and 28.7% of infants younger than 6 months of age were exclusively breastfed in twelve central and western provinces (2009) [10]. China initiated the National Basic Public Health Service Program in 2009 to improve essential public health services (including promotion of breastfeeding) in both urban and rural areas [11,12,13]. Only three studies have updated the recent national or local data on the prevalence of breastfeeding.…”
Section: Introductionmentioning
confidence: 99%
“…The degree of this limitation usually depends on the performance of the health care system in place: The more sophisticated the health care system, the more regulations are in place, which in turn limits the GPs practice location choices. China for example has a rather weak primary care system, whereas the United Kingdom and Germany have a rather strong primary care system [6, 22]. Bearing this in mind, our results only reflect the situation in a developed health care setting.…”
Section: Discussionmentioning
confidence: 82%
“…In this context, little is known about the factors associated with settlement decisions of GPs in metropolises. So far, numerous studies have focused on urban vs. rural comparisons of GP distribution and their impact on health inequity [1622]. Only few studies have investigated metropolitan areas in Germany [23, 24].…”
Section: Introductionmentioning
confidence: 99%